Discovery of Object Suspected of Cultural Heritage Olak Badar Sematang Pundung Temple - Noranda, Alfa (Regalia Institute, 2024)
The implementation of this research aims to record and map the potential of Olak Badar Sematang Pundung Temple in Kumpeh District, Muaro Jambi Regency. The existence of illegal activitis from treasure hunters on this site because there are several illegal excavation holes found on the site and abandoned. In an effort to preserve and save the Object of Suspected Cultural Heritage (ODCB) in the site area. So that later it can be processed for cultural heritage designation. In the Sematang Pundung Temple Site Mapping activity, which is in Tanjung Village, Kumpeh District, Muaro Jambi Regency, using quantitative and qualitative research methods. Such research methods in data collection and potential mapping activities are generally applied in archaeological research. From the results of field data collection, twenty-four (24) ODCB objects were found. Based on the results of data collection and potential mapping, it is known that the Sematang Pundung Temple Site is an area consisting of several sites and has objects suspected of cultural heritage. As an area that has ODCB findings, the sites in this area are vulnerable to illegal looting activities.